2002
DOI: 10.1063/1.1474609
|View full text |Cite
|
Sign up to set email alerts
|

Low-resistant and high-transparent Ru/Ni ohmic contact on p-type GaN

Abstract: We report a low-resistant and high-transparent Ru-based ohmic contact on p-type GaN through oxidation annealing under O2 atmosphere. A low resistivity of 4.5×10−5 Ω cm2 and high light transmittance (84.6%) were simultaneously obtained from oxidized Ru (50 Å)/Ni (50 Å) contact. The RuO2 formed on p-type GaN played a role in reducing the effective Schottky barrier height for injection of holes and NiO layer produced on the RuO2 acted as a diffusion barrier for the outdiffusion of released Ga and N atoms, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Jang and co‐workers also observed that the surface of their contacts based on Pt/Ru and Ru/Ni schemes remained smooth after annealing at 600 °C for 30 min, which is attributed to the thermodynamic stability of Ru. Parameters of these metal contacts on p‐GaN are listed in Table 1 .…”
Section: Metal Contactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jang and co‐workers also observed that the surface of their contacts based on Pt/Ru and Ru/Ni schemes remained smooth after annealing at 600 °C for 30 min, which is attributed to the thermodynamic stability of Ru. Parameters of these metal contacts on p‐GaN are listed in Table 1 .…”
Section: Metal Contactsmentioning
confidence: 99%
“…Following this consideration, another metal with good quality oxides, Ru, was investigated as a contact material on p‐GaN, since its metallic‐conducting oxide RuO 2 , with the rutile structure, has a large work function, low resistivity and excellent thermal stability. Jang et al used Ru intermediate layers on p‐GaN in their Ru/Ni and Pt/Ru contacts . They obtained a transparency of 84.6% at 460 nm (Ni/Ru) and 87.3% at 470 nm (Pt/Ru), respectively.…”
Section: High Transparency Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The ideal metal contact to p-GaN would have a work function greater than that of GaN (;6.5 eV to 7.5 eV). 3,4 For light emitting diodes (LEDs), extraction of the light from the device is paramount to device efficiency and several contact schemes using semitransparent contacts, including oxidized Ni/Au, [5][6][7][8][9][10][11][12] Ru/Ni, 13 Pd/Ni, 14 NiAu, and Al or Ag, 15 indium-tin-oxide-based, 16 and ZnObased, 17 have been reported. The most detailed studies have been reported on the oxidized thin Ni/Au system.…”
Section: Introductionmentioning
confidence: 99%
“…Annealing in the range of 400-750 o C with these leads to typical contact resistances in the 10 -2 ~ 10 -3 Ω.cm 2 range. This anneal serves to increase the hole concentration of the p-GaN by removing hydrogen, which acts as a compensator to the Mg dopant, from the semiconductor [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The anneal also can promote the formation of low resistance interfacial phases.…”
mentioning
confidence: 99%